Curriculum Management in Improving the Quality of Graduates at PKBM Manarul Hidayah Batumarta OKU - Yuni Lestari; Yudan Hermawan; Adin Ariyanti Dewi (Assyfa Journal of Islamic Studies, 2026)
The purpose of this study is to describe curriculum management in improving the quality of graduates at the Manarul Hidayah Batumarta OKU Community Learning Center (PKBM). The study used a descriptive qualitative approach. Data collection was conducted through interviews, observations, and documentation involving the PKBM head, curriculum managers, tutors, and students. The research findings indicate that curriculum management is carried out through planning, organizing, implementing, and evaluating an integrated curriculum that combines general and religious learning, as well as skills. The curriculum is designed flexibly to meet student needs, referring to the Independent Curriculum and the tahfidz program. Evaluation is implemented periodically to accumulate levels of academic growth and student character. This curriculum management contributes to improving the quality of graduates who are religious, have character, and possess balanced academic competencies